Impact of COVID-19 lockdown on smoking and vaping: systematic review and meta-analysis. (May 2023) - Bakaloudi, Dimitra Rafailia; Evripidou, Kleo; Siargkas, Antonios; Breda, Joao; Chourdakis, Michail
Abstract: Objectives: COVID-19 and the implementation of lockdowns have impacted daily lives worldwide. This systematic review and meta-analysis aimed to investigate the impact of lockdowns on the smoking and vaping behaviours of adults during the pandemic. Study design: This was a systematic review and meta-analysis. Methods: A systematic literature search was conducted up to 28 April 2022 in the following databases: PubMed, Embase and Web of Science. Results: In total, 77 studies met the inclusion criteria for this review. In 34 studies, an increase in smoking behaviour was reported for the majority of participants; however, in 21 and 18 studies, 'no change' and 'decrease' in smoking were the predominant responses, respectively. The results from the meta-analysis, which examined the change in the number of cigarettes smoked per day, showed no difference between the pre- and post-lockdown periods: 0.81 weighted mean difference (95% confidence interval, −0.59 to 2.21). Regarding vaping, three of seven studies reported an increase in smoking for the majority of participants, whereas 'no change' and 'decrease' were the predominant answers in the other four studies. Conclusions: The results show that lockdowns led most participants to increase smoking/vaping, whereas a decrease or cessation of smoking/vaping was only reported in the minority of participants. Attention should be given to the non-communicable diseases that could arise as a result of the increase in smoking/vaping during lockdowns, and further research in this area is needed.